HISTORY OF INTERNATIONAL RELATIONS AND ITS DEVELOPMENT IN THE DIGITAL ERA - Solieva Dilfuza Nosirjanovna (Western European Studies, 2025)
This article examines the historical evolution of international relations (IMO) and emphasizes the relevance of understanding them in the modern digital world, where information technologies play a decisive role in diplomacy, conflict resolution, and global governance. Using relevant analysis and historical examples, the study examines how the digital age has changed traditional diplomatic practice, creating new challenges and opportunities for states and non-governmental entities.
Keywords: evolution; digital technologies; diplomacy